Diagnostic Accuracy of Female Pelvic Ultrasonography in Differentiating Precocious Puberty From Premature Thelarche: A Systematic Review and Meta-analysis - Nguyen, Nam Nhat; Huynh, Linh Ba Phuong; Do, Minh Duc; Yang, Tien Yun; Tsai, Meng-Che; Chen, Yang-Ching (Frontiers in Endocrinology, 2021)
Background The gonadotropin-releasing hormone (GnRH) stimulation test is the benchmark for diagnosing precocious puberty (PP). However, it is invasive, time-consuming, costly, and may create an unpleasant experience for participants. Moreover, some overlaps may occur between PP and premature thelarche (PT) in the early stage of PP. Female pelvic ultrasonography may provide additional information to help differentiate PP from PT and subsequently initiate early treatment. In this study, we aimed to first directly compare pelvic ultrasonography parameters between PP and PT groups and secondly, investigate their diagnostic accuracy compared with the GnRH stimulation test. Methods A systematic search of the PubMed/MEDLINE, EMBASE, Scopus, and Cochrane Library databases was performed up to March 31, 2021. All types of studies, except for case reports and review articles, were included. The GnRH stimulation test was used to confirm PP diagnosis. Those whose organic conditions might cause PP were excluded. The mean, standard deviation, sensitivity, and specificity of each parameter were documented. Forest plots were constructed to display the estimated standardized mean differences (SMDs) from each included study and the overall calculations. A bivariate model was used to calculate the pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), and diagnostic odds ratio (DOR). Results A total of 13 studies were included for analysis. The SMDs (95% confidence interval – CI) in ovarian volume, fundal-cervical ratio, uterine length, uterine cross-sectional area, and uterine volume between PP and PT groups were 1.12 (0.78–1.45; p < 0.01), 0.90 (0.07–1.73; p = 0.03), 1.38 (0.99–1.78; p < 0.01), 1.06 (0.61–1.50; p < 0.01), and 1.21 (0.84–1.58; p <0.01), respectively. A uterine length of 3.20 cm yielded a pooled sensitivity of 81.8% (95% CI 78.3%–84.9%), specificity of 82.0% (95% CI 61.0%–93.0%), PLR of 4.56 (95% CI 2.15–9.69), NLR of 0.26 (95% CI 0.17–0.39), and DOR of 19.62 (95% CI 6.45–59.68). The area under the summary receiver operating characteristics curve was 0.82. Conclusion Female pelvic ultrasonography may serve as a complementary tool to the GnRH stimulation test in differentiating PP from PT. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021232427, ID: CRD42021232427.